KEBERADAAN FUNGI PELARUT FOSFAT PADA TANAH BEKAS KEBAKARAN HUTAN DI KABUPATEN SAMOSIR - Wika Astuti Sagala; Deni Elfiati; Delvian Delvian (Peronema Forestry Science Journal, 2015)
The forest fire effect chemical, psysical and biological propesties of the soil. In the biological of soil, forest fire also effect the existence of phosphates solubilizing fungi. This research was conducted to determine the presence of Phosphates Solubilizing Fungi  in the former soil of fired forest by the time of the fire in Samosir Regency. Soil samples taken from former soil of fired forest and unfire forest at a dept 0 – 20 cm around rhizosfir. Soil analysis carried out in Research and Technology of University of North Sumatera along with isolation and identification phosphates solubilizing fungi at the Laboratory Soil Biology Agroekoteknologi Studies Program Faculty of Agriculture, University of North Sumatera. The result showed that there were similitary and differences phosphates solubilizing fungi in former soil of fired forest and unfire forest. Phosphates solubilizing fungi consisting of 2 fungi genus there are Aspergillus and Penicillium. Keywords: Forest Fire, Phosphates Solubilizing Fungi